1981
DOI: 10.1038/ki.1981.201
|View full text |Cite
|
Sign up to set email alerts
|

Children with urinary infection: A comparison of those with and those without vesicoureteric reflux

Abstract: Wnereas milk-(or formula-)feeding neutralizes the gastrlc con-tent(pH>4), gastric pH monitorlng can be used studying the gast.ric anacidity, and subsequently the gastric eklptyjng, tlme (Sutphen, AJDC 1986;140:1062-1064). Using a new technique, extended simultaneous esophageal and gastric pH monitorlng, we measured the postcibal time gastric pH was > 4 in 11 asymptomatic infants according to a double-blind cross-over technique. Two isocaloric formulae with a different fat concentration were studied. The compos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
41
0
6

Year Published

1985
1985
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 134 publications
(52 citation statements)
references
References 14 publications
5
41
0
6
Order By: Relevance
“…No presente estudo, a porcentagem de pacientes com cicatriz renal foi semelhante à descrita na literatura, cuja incidência varia entre 30% a 70% [15][16][17][18][19] . A variação desta incidência em parte é influenciada pelo método de diagnós-tico da cicatriz renal.…”
Section: Discussionunclassified
“…No presente estudo, a porcentagem de pacientes com cicatriz renal foi semelhante à descrita na literatura, cuja incidência varia entre 30% a 70% [15][16][17][18][19] . A variação desta incidência em parte é influenciada pelo método de diagnós-tico da cicatriz renal.…”
Section: Discussionunclassified
“…These children cannot be identified clinically. 9 One prospective study found that the highest rates of renal scarring after an episode of pyelonephritis occurred between the ages of 1-5 years. 10 Older children with more severe presentations may need careful investigation.…”
Section: Commentmentioning
confidence: 99%
“…Many recent studies 1,2,3,4 focused on the UTI effect on the children. Durbin 5 in a review of epidemiology of UTI in developing countries identified obstructive uropathy & immuno-compromised child as risk factors for UTI.…”
Section: Introductionmentioning
confidence: 99%